Chiral 3D DNA origami structures for ordered heterologous arrays. Issue 16 (16th July 2021) - Islam, Md. Sirajul; Wilkens, Gerrit David; Wolski, Karol; Zapotoczny, Szczepan; Heddle, Jonathan Gardiner
Abstract : Chiral DNA structures can tile snugly together to form regular structures that alternate between left-and right-handed forms. Abstract : The DNA origami technique allows the facile design and production of three-dimensional shapes from single template strands of DNA. These can act as functional devices with multiple potential applications but are constrained by practical limitations on size. Multi-functionality could be achieved by connecting together distinct DNA origami modules in an ordered manner. Arraying of non-identical, three-dimensional DNA origamis in an ordered manner is challenging due for example, to a lack of compatible rotational symmetries. Here we show that we can design and build ordered DNA structures using non-identical 3D building blocks by using DNA origami snub-cubes in left-handed and right-handed forms. These can be modified such that one form only binds to the opposite-handed form allowing regular arrays wherein building blocks demonstrate alternating chirality.